ANALYSIS OF PACKAGE INSERTS OF ANTIMICROBIAL DRUGS UTILISED IN A TERTIARY CARE HOSPITAL OF NORTH KARNATAKA - INGALE, ANAND M.; PALABHAVI, PRIYANKA S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2023)
Objective: To evaluate the package inserts of antimicrobial drugs utilized in a tertiary care Hospital of North Karnataka Methods: A cross-sectional, observational, prospective study was undertaken to analyze the package inserts of antimicrobial drugs utilized in a tertiary care hospital in North Karnataka for two months. 218 that belonged to antimicrobials were included in our study and analyzed based on criteria mentioned in Schedule D of the Drug and Cosmetic Act of 1945. Results: None of the Package Inserts analyzed by us adhered to the standard guidelines. Legibility, Approved generic name of active ingredients, and Content of active ingredient per dosage was mentioned in all. In contrast, the least mentioned criteria included References (n=2) and Retail price of the drug (n=9). Conclusion: Updating the existing ones and stricter adherence to the PI with the standard guidelines will achieve better quality and, in turn, improve health care in our society, especially by these antimicrobial agents, which can prevent the development of antimicrobial resistance.